Peak Oil and the New, Local Economy (Sustainability in Debate, 2013)
RUBIN, Jeff. Why Your World is About to Get a Whole Lot Smaller. Toronto: Vintage Canada, 2010. 322 p. Source Notes, Index. ISBN 978-0-307-357526.